MANAJEMEN DOKUMEN PRODUK BIRO HUKUM DAN HAM SEKRETARIAT DAERAH PROVINSI KEPULAUAN RIAU - Zuhdi Arman; Agus Riyanto (Ensiklopedia of Journal, 2023)
This study aims to determine the management of legal product documents in legal counseling activities in the Legal and Human Rights Bureau of the Regional Secretariat of the Riau Islands Province. The method used is qualitative research with a study approach. Data collection techniques are carried out through observation and literature studies. Data analysis techniques are carried out using data analysis techniques, according to Miles and Huberman, namely data reduction, data presentations, and conclusions. The results showed that the activity of handling legal product documents in the Legal and Human Rights Bureau in the Regional Secretariat of the Riau Islands Province followed the documentation rules, which included recording which included formulation activities, organizing, which included preparation and storage activities, and socialization included extension activities and socialization. Based on the results of the study, it can be concluded that the documentation rules have managed legal product documents in the Legal and Human Rights Bureau of the Regional Secretariat of the Riau Islands Province.Keywords: Documents, products, laws, regions